Argument and persuasion in Descartes' Meditations - Cunning, David (New York ; Oxford : Oxford University Press, 2010)
Descartes' 'Meditations on First Philosophy' has proven to be not only one of the canonical texts of Western philosophy, but also the site of a great deal of interpretive activity in scholarship on the history of early modern philosophy over the last two decades. David Cunning's monograph proposes a new interpretation.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Sept. 7, 2010).
Keywords: d; Methodology; First philosophy; God -- Proof, Ontological